2005
DOI: 10.1097/00001813-200502000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of non-small cell lung cancer with gefitinib (???Iressa???, ZD1839): the Greek experience with a compassionate-use program

Abstract: This is a retrospective analysis of 150 patients with advanced non-small cell lung cancer who had failed prior treatment or were unfit for chemotherapy and were treated with oral gefitinib ('Iressa', ZD1839; AstraZeneca) 250 mg/day. Thirty-two patients who received gefitinib for 3 weeks or less were not included in the analysis. For the remaining 118 evaluable patients, the mean age was 63.1 years; most patients had received prior chemotherapy (97.5%), Eastern Cooperative Oncology Group performance status scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Correlation between EGFR expression and a higher likelihood of response to EGFR TKI was postulated, but dismissed in small trials [37][38][39]. In the BR.21 trial lack of EGFR expression was associated with a decreased benefit from erlotinib when compared with patients treated with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation between EGFR expression and a higher likelihood of response to EGFR TKI was postulated, but dismissed in small trials [37][38][39]. In the BR.21 trial lack of EGFR expression was associated with a decreased benefit from erlotinib when compared with patients treated with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhoea, mostly grade 1 -2, has been reported at an incidence of 12.8 -42% in compassionate use studies [36,38]. The incidence of grade 3 -4 diarrhoea in these studies ranged from 1 -4.2% [34,37]. Shah et al, advise their patients to take two 2 mg loperamide tablets at the onset of diarrhoea followed by one 2 mg tablet after every loose bowel movement up to a maximum of 10 tablets per day [46].…”
Section: Diarrhoeamentioning
confidence: 99%
“…All adverse effects were grade 1 -2 except one patient who experienced a grade 3 rash. A review of adverse effects reported in compassionate use studies and the expanded access programme is presented in Table 3 [22,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of protein expression levels by immunohistochemistry (IHC) has so far yielded disappointing results. For example, in a retrospective analysis of 118 non-small cell lung cancer (NSCLC) patients who received gefitinib, Razis et al [2] found that efficacy did not correlate with tumor EGFR overexpression. Amann et al [3] demonstrated strong response to anti-EGFR treatment in an EGFR-amplified and EGFR-mutated NSCLC cell line but only an intermediate effect in another EGFR wild-type cell line with strong EGFR protein levels.…”
Section: Introductionmentioning
confidence: 99%